(untitled) (Research, Society and Development, 2022)
Objective: To verify the ambulatory care sensitive conditions prevalence among older adults in the years 2008 and 2018 and associated variables. Methods: Cross-sectional quantitative observational study with data from the national health information system carried out in the city of Passo Fundo-RS in the years 2008 and 2018, with a sample composed of 9,064 authorizations for hospital admissions. The variables age, sex, race/color, address and procedure code were evaluated. The outcome of hospitalizations for sensitive causes was defined based on ICD-10 of the authorized procedure according to the Brazilian Sensitive Conditions to Primary Care List. Descriptive analyzes were performed and for the associations the chi-square test and Fisher’s exact tests were applied. Results: Ambulatory care sensitive conditions of the elderly were significant, higher in 2008 when compared to 2018, 33.6% and 27.9%, respectively (p<0.001). The prevalence of ambulatory care sensitive conditions was 33.6% in 2008, with a reduction to 27.9% in 2018 (p <0.001). In 2008, hospitalizations were more prevalent in aged between 70 and 79 and the prevalence was higher in individuals living in the area covered by the Family Health Strategy. In the year of 2018, hospitalizations of elderly people aged 90 years or older were higher (p <0.001), as were diseases of the circulatory and respiratory systems. The reduction of the ambulatory care sensitive conditions from 2008 to 2018 was significant. Conclusion: The reduction of the ambulatory care sensitive conditions from 2008 to 2018 was significant. New studies are needed on the subject and the resolution of Primary Care.